CXCR4 signaling in macrophages contributes to periodontal mechanical hypersensitivity in Porphyromonas gingivalis-induced periodontitis in mice. Issue 1 (January 2017) - Nagashima, Hidekazu; Shinoda, Masamichi; Honda, Kuniya; Kamio, Noriaki; Watanabe, Masahiro; Suzuki, Tatsuro; Sugano, Naoyuki; Sato, Shuichi; Iwata, Koichi
Background: Periodontitis is an inflammatory disease accompanied by alveolar bone loss and progressive inflammation without pain. However, the potential contributors eliminating pain associated with gingival inflammation are unknown. Results: we examined the involvement of CXC chemokine receptor type 4 (CXCR4) on the mechanical sensitivity of inflamed periodontal tissue, using a mouse model of periodontitis established by the ligation of the tooth cervix of a maxillary second molar and inoculation with Porphyromonas gingivalis (P. gingivalis) . Infiltration of inflammatory cells into gingival tissue was not observed following the inoculation. Under light anesthesia, the mechanical head withdrawal threshold (MHWT) on the buccal gingiva was measured using an electronic von Frey anesthesiometer. No significant changes in MHWT were observed in the mice with P. gingivalis -induced periodontitis during the experimental period. Continuous administration of CXCR4 neutralizing antibody to the gingival tissue significantly decreased MHWT and increased the number of gingival CXCR4 immunoreactive macrophages in the periodontitis group. Nitric oxide metabolites in the gingival tissue were significantly increased after the inoculation of P. gingivalis and were reduced by gingival CXCR4 neutralization. Gingival L-arginine administration induced gingival mechanical allodynia in naive animals. Moreover, the decrease in MHWT after treatment with P. gingivalis and CXCR4 neutralization was partially reversed by nitric oxide synthase inhibition in the gingival tissue. Nuclear factor-kappa B was expressed in infiltrating macrophages after inoculation of P. gingivalis and administration of the nuclear factor-kappa B activator betulinic acid induced gingival mechanical allodynia in naive mice. Conclusions: These findings suggest that CXCR4 signaling inhibits nitric oxide release from infiltrating macrophages and is involved in modulation of the mechanical sensitivity in the periodontal tissue in P. gingivalis -induced periodontitis.